The Plant Growth of Malonan 1 Pepper (Piper nigrum L.) Cutting on Different Planting Media Composition and Coconut Water Dosage: Pertumbuhan Stek Tanaman lada (Piper nigrum L.) Malonan 1 Pada Komposisi Media Tanaman dan Dosis Air Kelapa Yang Berbeda - Hamidah Hamidah; Tutik Nugrahini; Marlina (Universitas Widya Gama Mahakam, 2023)
The purpose of this study was to determine the effect of different planting medium compositions and concentrations of coconut water on the growth of pepper cuttings. This research was carried out for 3 months, starting from January to April 2020. This research site is in the experimental garden of the Faculty of Agriculture, Widya Gama University, Mahakam Samarinda. This research method used a randomized block design with 3 x 4 factorial experiments consisting of 3 replications. The first factor is the planting medium (M) which consists of 3 levels, namely: M0 Control (4 kg), M1 Topsoil + Goat Manure (3: 1) and M2 Topsoil + Goat Manure Fertilizer + Husk Charcoal (2: 1: 1) The second factor is Coconut Water which consists of 4 levels, namely: K0 (control), K1 (150 ml / 500 ml water), K2 (250 ml / 500 ml water) K3 (350 ml / 500 ml water). The variables analyzed were the number of shoots, plant height, and root length. The results of this study indicate that the best planting medium is found in treatment M2 = Topsoil (2 Kg) + goat manure (1 kg) + rice husk (200 g) and the best concentration of coconut water is found in treatment K3 = (350 ml / 500 ml of water) has the best effect on the growth of the pepper (Piper nigrum L.) Malonan 1 Keywords: Malonan 1, Growing Media, Coconut Water